2017
DOI: 10.1002/admi.201601219
|View full text |Cite
|
Sign up to set email alerts
|

3D Hierarchically Porous Graphitic Carbon Nitride Modified Graphene‐Pt Hybrid as Efficient Methanol Oxidation Catalysts

Abstract: reducing the amount of Pt, for example, to construct hybrids electrode materials incorporating Pt-based nanocatalysts into carbon support materials, such as porous carbons, [5] carbon nanotubes (CNT), [6,7] and graphene sheets. [8] To improve the surface of chemically inert carbon materials as well as to introduce microspores, several different strategies have been investigated. A useful strategy is chemical activation by using alkali hydroxides as activating agents for pulling in microspores with narrow dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 108 publications
1
17
0
Order By: Relevance
“…Zhang et al used C-N covalent bonds to combine g-C 3 N 4 and reduced graphene oxide into three-dimensional porous carbon nanocomposite carriers for loading Pt nanoparticles to form 3D Pt-g-C 3 N 4 -rGO and exhibit excellent methanol electrocatalytic performance. 24,25 Zhong et al synthesized Mn-Fe@g-C 3 N 4 by the in situ wrapping of g-C 3 N 4 on MIL-101(Fe) and showed excellent initial potential and half-wave potential of the reduction-oxidation reaction. 26 Li et al first proposed the preparation of g-C 3 N 4 -coated carbon black composite as a carrier for the electrocatalytic oxidation reaction of methanol and found that the catalytic activity was 2.1 times that of pure carbon black carrier.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al used C-N covalent bonds to combine g-C 3 N 4 and reduced graphene oxide into three-dimensional porous carbon nanocomposite carriers for loading Pt nanoparticles to form 3D Pt-g-C 3 N 4 -rGO and exhibit excellent methanol electrocatalytic performance. 24,25 Zhong et al synthesized Mn-Fe@g-C 3 N 4 by the in situ wrapping of g-C 3 N 4 on MIL-101(Fe) and showed excellent initial potential and half-wave potential of the reduction-oxidation reaction. 26 Li et al first proposed the preparation of g-C 3 N 4 -coated carbon black composite as a carrier for the electrocatalytic oxidation reaction of methanol and found that the catalytic activity was 2.1 times that of pure carbon black carrier.…”
Section: Introductionmentioning
confidence: 99%
“…A 3D hierarchical porous structure has been regarded as one of the most promising electrocatalysts and electrocatalyst supports. The micropores and mesopores could increase the active sites, and the macropores could promote the mass transport toward and away from the active sites . To date, the common routes for fabricating hierarchical carbon structures typically involve templates, such as porous alumina, silica, zeolite, and polystyrene .…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous catalysis is a surface process involving most, if not all, constitutional atoms at or near the catalyst surface. For noble metal catalysts, the nanostructures of metal clusters with dimensions in the range of a single metal atom to the nanoparticles (>2 nm) have gained great interest in order to lower the cost of the catalysts and exploit efficient use of catalytically active components. , For instance, Pt-based catalysts possess unique and significant electrocatalytic activities toward methanol oxidation reactions, but the high costs and the scarcity of Pt sources seriously block their large-scale commercial applications. , Small nanoclusters are therefore extremely desirable in improving Pt utilization efficiency. Generally, the size of metal clusters is also one of the most critical factors that dictate the performances of a catalyst .…”
mentioning
confidence: 99%
“…The material, in fact, contains periodic tri- s -triazine subunits coupled via the planar tertiary amino groups, resulting in uniform structural N-coordinating cavities. The high level of pyridinic nitrogen in each cavity is capable of tenaciously capturing metal ions owing to the nature of abundant electron lone pairs. Such strong electronic interactions have extensively been regarded as a crucial tool to manipulate the electronic structures of the metal nanoclusters and thus to interact with the intermediates during the catalytic reactions. , More importantly, g-C 3 N 4 offers abundant and homogeneous nitrogen coordinators, which gives rise to many inherent advantages, including sustaining metal atoms with their neutral states, efficiently accumulating surface polarization charges on metal atoms, , and affording more accurate information for the identification of catalytically active sites. ,, Unfortunately, its low electrical conductivity dramatically deteriorates the electrocatalytic processes, limiting their applications in the field of electrochemistry. Tremendous efforts have been made in exploring effective strategies to improve its electron transferability, such as designing advanced nanostructures, , incorporating mesoporous structures, , combining with carbon materials, , and heteroatom doping. , However, developing a strongly coupled g-C 3 N 4 -based composite support with fast electron mobility, robust structural stability, and mechanical strength is still highly desirable.…”
mentioning
confidence: 99%
See 1 more Smart Citation